An optimal far‐field radiation pattern synthesis of time‐modulated linear and concentric circular antenna array. (25th July 2019) - Das, Avishek; Mandal, Durbadal; Kar, Rajib
Abstract: In this paper, an optimal far‐field radiation pattern synthesis by using time modulation technique is carried out for linear antenna array (LAA), and concentric circular antenna array (CCAA) designs using a stochastic optimization method called grey wolf optimization (GWO). An improved far‐field radiation characteristic mainly depends on the synthesis of low side lobe level (SLL) and narrow first null beam width (FNBW). A low SLL is a requirement to reduce the interference by the other systems operating in the same frequency band. A narrow FNBW is necessary to obtain a high directivity. In time modulation technique, "time" has a most significant role. It is considered as the fourth‐dimensional parameter as it plays the role of an additional degree of freedom to achieve an improved radiation pattern. The time‐modulated antenna array (TMAA) radiates at various harmonic frequencies for the periodic switching time sequence. In this paper, the generation of radiation pattern only at the fundamental/central frequency and at its first two harmonic frequencies are considered. The GWO algorithm is a flexible and robust search algorithm and is applied here to find out the optimum sets of switching on‐time duration for each array element and to determine the optimum inter‐element separation between two array elements of the 16‐element time‐modulated linear antenna array (TMLAA) and the nine‐ring time‐modulated concentric circular antenna array (TMCCAA). The GWO algorithm‐based results show a substantial improvement in far‐field radiation pattern synthesis compared with the uniform radiation pattern and those of the methods reported in state‐of‐the‐art literature.